Glasgow aneurysm scores in patients undergoing open surgical procedure for aortic aneurysm. (June 2015) - Ozen, Anil; Unal, Ertekin Utku; Kubat, Emre; Turkcan, Basak Soran; Caliskan, Aytac; Aytekin, Bahadir; Aksoyek, Aysen; Birincioglu, Cemal Levent; Pac, Mustafa
Background: To assess the applicability of the Glasgow aneurysm score (GAS) in patients with aortic aneurysm undergoing an elective open surgical procedure in our hospital. Materials and methods: A total of 105 patients undergoing elective open surgical procedure between January 2006 and June 2012 were evaluated retrospectively. Glasgow aneurysm score (GAS) was calculated as age+7 points for myocardial disease, +10 points for cerebrovascular disease, and +14 points for renal disease. The best cut-off value for GAS was determined using the ROC curve analysis. Results: The hospital mortality rate was 3.8% (4 patients). GAS was significantly lower in patients who survived the operation (76.05 ± 14.71 vs. 92.0 ± 10.8 respectively, p = 0.031). The ICU stay was also significantly lower in patients who survived the operation (2.37 ± 5.23) compared to the nonsurvivors (25.67 ± 13.80, p = 0.001). No significant difference was observed regarding age, duration of hospital stay, and aortic diameter. The area under the ROC curve was 0.818 and for a 100% sensitivity rate, the cut-off value for GAS was 77.5 with a 58.4% specificity rate ( p = 0.031). All patients with a GAS < 77.5 were alive after surgery. Conclusion: The GAS appears to be a reliable clinical predictor for in hospital mortality following elective repair of abdominal aortic aneurysm following open surgical procedure.